Twilight Volume 1 / : the graphic novel - Kim, Yŏng-bin, 1976-; Meyer, Stephenie, 1973- (New York : Yen Press, 2010)
A graphic novel adaptation of Stephenie Meyer's "Twilight" in which seventeen-year-old Bella leaves Phoenix to live with her father in Forks, Washington, where she meets an exquisitely handsome boy at school for whom she feels an overwhelming attraction and who she comes to realize is not completely human.
Young Adult.
Young Adult
Keywords: Meyer, Stephenie, -- 1973- -- Adaptations; Meyer, Stephenie, -- 1973- -- Adaptations; Cullen, Edward (Fictitious character) -- Comic books, strips, etc -- Fiction; High schools -- Comic books, strips, etc -- Fiction; Man-woman relationships -- Comic books, strips, etc -- Fiction; Swan, Bella (Fictitious character) -- Comic books, strips, etc -- Fiction; Vampires -- Comic books, strips, etc -- Fiction; Comic books, strips, etc; Cullen, Edward (Fictional character) -- Comic books, strips, etc -- Fiction; Graphic novels; High schools -- Comic books, strips, etc -- Fiction; Horror graphic novels; Love stories; Man-woman relationship -- Comic books, strips, etc -- Fiction; Manga; Swan, Bella (Fictional character) -- Comic books, strips, etc -- Fiction; Vampires -- Comic books, strips, etc -- Fiction; Washington (State) -- Comic books, strips, etc -- Fiction; Washington (State) -- Comic books, strips, etc -- Fiction; Graphic novels; Horror comic books, strips, etc; Love stories